HARAKATLI OʻYINLARNI TASHKIL QILISH SHAKLLARI VA METODIKASI - Saparbaev, E. (SCIENCE and SOCIETY, 2024)
The article presents examples of forms of organizing outdoor games, methods of conducting outdoor games in physical education classes. In order for students to better understand the content of the game, it is necessary to perform some of its actions along with an oral explanation from the leading specialist.